A Literature Review: Innovative Leadership Style - Andi Indriani Ibrahim; Syahbudin Adam; Indah Fitriani; Risna; Rahmat Lapaduai; Indriani; Yusniyanti (Jurnal Sinar Manajemen, 2025)
This study aims to identify and analyse the role of innovative leadership styles in driving organisational performance across various sectors in Indonesia, based on a review of 20 national journals published between 2021 and 2025. The results of the literature review show that innovative leadership consistently has a positive effect on improving employee performance, organisational culture, and innovation capabilities in the education, health, government, and creative industries sectors. Leaders with innovative leadership styles are characterised by their ability to adapt to change, encourage member participation, create an open work climate, and initiate creative solutions. In addition, innovative leadership has been proven to strengthen cross-sector collaboration and is a key factor in the success of organisations facing the challenges of the digital era. These findings reinforce that the development of innovative leadership styles needs to be a strategic priority in efforts to strengthen the competitiveness of organisations in Indonesia.